2019
DOI: 10.2478/ijek-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the University in the Entrepreneurial Intention of Female Students

Abstract: Many researchers have studied gender differences in the entrepreneurial intention of students by analyzing the influence of several intrinsic and extrinsic factors on the antecedents of entrepreneurial intention. Fewer researchers have analyzed the influence of the university’s environment and support system on the precursors of the entrepreneurial intention of students in general and of female students in particular. This study aims to fill that gap by analyzing the influence of the university’s environment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 89 publications
3
16
0
Order By: Relevance
“…In the literature, this variable has contradicting results, while some studies have supporting evidence of this variable on EIs, with other studies showing no effect of ES on EI of the students. The finding of this study is consistent with research done by Bazan et al (2019), Nguyen (2020) and Chen et al (2013) who found no significant effect of ES on EI in their studies. While various other studies by Boldureanu et al (2013), Franke and Luthje (2004), Schwarz et al (2009) and Yu Cheng et al (2009), Matlay et al (2010) supported the relationship of ES on EI.…”
Section: Discussionsupporting
confidence: 93%
“…In the literature, this variable has contradicting results, while some studies have supporting evidence of this variable on EIs, with other studies showing no effect of ES on EI of the students. The finding of this study is consistent with research done by Bazan et al (2019), Nguyen (2020) and Chen et al (2013) who found no significant effect of ES on EI in their studies. While various other studies by Boldureanu et al (2013), Franke and Luthje (2004), Schwarz et al (2009) and Yu Cheng et al (2009), Matlay et al (2010) supported the relationship of ES on EI.…”
Section: Discussionsupporting
confidence: 93%
“…4. The study adds to the existing knowledge about the causal relationship between innovativeness and entrepreneurial intention even though many of the previous studies mainly mentioned that entrepreneurial passion or attitude towards entrepreneurship is the main predictor of entrepreneurial intention (Maziriri, Maramura, & Nzewi, 2019;Bazan et al, 2019;Doan & Phan, 2020;Jena, 2020;Nan, Wei, & Lim, 2020). However, Covin and Slevin (1990) discussed the three key characteristics of entrepreneurship, namely, innovativeness, risk taking, and proactiveness.…”
Section: Discussionmentioning
confidence: 90%
“…e development trend of big data is not only a positive promotion for college student entrepreneurs but also a great benefit for college entrepreneurial instructors [14]. e era of big data provides a new direction for college student entrepreneurs.…”
Section: Complexitymentioning
confidence: 99%